Prenatal sonographic diagnosis of multicystic congenital mesoblastic nephroma. Issue 1 (27th December 2012) - Esmer, Aytul Corbacioglu; Kalelioglu, Ibrahim; Kilicaslan, Isin; Gun, Feryal; Ziylan, Orhan
<x xml:space="preserve">Abstract</x> The authors report an unusual presentation of congenital mesoblastic nephroma as a multilocular cystic renal lesion. Prenatal sonography revealed a unilateral, encapsulated, multilocular cytic mass with solid components measuring 5.7 × 5.4 × 4.3 cm in the left renal fossa. There was no increase in vascularity and no signs of hydrops fetalis. On the forth postnatal day left‐sided radical nephrectomy was performed and histopathological examination revealed cellular type congenital mesoblastic nephroma. A multicystic appearance is rare as the vast majority of prenatally diagnosed congenital mesoblastic nephroma cases presented in the literature are of the classic type with solid homogenous or heterogenous appearence. © 2012 Wiley Periodicals, Inc. J Clin Ultrasound41:59–61, 2013